Dinamika Jasa Pendidikan Dan Pentingnya Pemasaran Jasa Pada Pendidikan - Abdullah Muqopie; Najmi Muhajir, Nur Muhammad; Mu’in, Abdul (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2023)
Marketing in the broadest sense is setting goals for accumulating profits to achieve the goals of an organization or institution, an understanding that is oriented towards accumulating profits, making the goal setting in question oriented towards market or customer needs whose ultimate goal is accumulating profits. Marketing education here is defined not as an organization or institution, but education is classified as a "non-profit oriented" service marketing or "non-profit company", where this educational institution does not seek profit alone, for the prosperity of the administrators or owners of the institution. The profits here are intended to improve the quality of services to the community as an effort to increase the number of candidates or students who are interested in enrolling in schools or educational institutions. The method used by researchers is a qualitative method. In this research, a descriptive-analytic approach is used to explore certain meanings using literature review. The dynamics of marketing services in educational institutions is a process that must be carried out by schools or madrasas to provide satisfaction to staff and the community. In marketing services that are "non-profit oriented" or "non-profit companies" there are three, namely; must understand the target market, good communication and interaction, provide opportunities for feedback, criticism and suggestions. These three things are the common thread to achieve the goal, namely "trust of partners or society in organizations or educational institutions.